Annual update of pediatric digestive diseases. (February 2011) - Oliva-Hemker, Maria; Yeung, Karla Au; Cuffari, Carmen; Scheimann, Ann; Wilson, Lindsay
The 24th Annual Meeting of the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition provided a comprehensive overview of pediatric digestive diseases. The meeting and its adjunct events, including a postgraduate course and 1-day symposium, enabled a diverse group of physicians, trainees and nurses to have the opportunity to discuss the latest developments in pediatric gastrointestinal, liver and nutritional disorders.